2023
DOI: 10.1021/acs.organomet.2c00640
|View full text |Cite
|
Sign up to set email alerts
|

Stability and Solution Behavior of [(dpp-Bian)Ln] and [(dpp-Bian)LnX] (Ln = Yb, Tm, or Dy; X = I, F, or N3)

Abstract: Treatment of an excess of ytterbium metal with dpp-Bian {dpp-Bian = 1,2-bis[(2,6-diisopropylphenyl)imino]acenaphthene} in the presence of 0.5 equiv of iodine resulted in a mixture of [(dpp-Bian)2–Yb2+(DME)2] (1) along with [YbI2(DME)2]2 and an over-reduced byproduct [(dpp-Bian)3–Yb2+I(DME)Yb2+(DME)2] (2). Oxidation of 1 with iodine is accompanied by electron transfer from the ligand to the metal atom to give [(dpp-Bian)−Yb2+I(THF)2]2 (3). Azide complexes [(dpp-Bian)2–Yb3+N3(DME)]6 (4) and [(dpp-Bian)2–Yb3+N3(T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 95 publications
0
5
0
Order By: Relevance
“…The simultaneous presence of a metal ion, which is able to exist in various oxidation states, and a redox-active ligand in a complex generally allows for a range of possible transformations through intra- or intermolecular routes. A striking example of intramolecular reactivity of such complex systems is the reversible electron transfer from metal to ligand, as reported for the ytterbium complexes [(dpp-Bian)­Yb II (dme)­Br] 2 , [(dpp-Bian)­Yb III (dme)­Cl]­[(dpp-Bian)­Yb II (dme)­Cl], and [(dpp-Bian)­Yb II I­(THF) 2 ] 2 …”
Section: Introductionmentioning
confidence: 79%
“…The simultaneous presence of a metal ion, which is able to exist in various oxidation states, and a redox-active ligand in a complex generally allows for a range of possible transformations through intra- or intermolecular routes. A striking example of intramolecular reactivity of such complex systems is the reversible electron transfer from metal to ligand, as reported for the ytterbium complexes [(dpp-Bian)­Yb II (dme)­Br] 2 , [(dpp-Bian)­Yb III (dme)­Cl]­[(dpp-Bian)­Yb II (dme)­Cl], and [(dpp-Bian)­Yb II I­(THF) 2 ] 2 …”
Section: Introductionmentioning
confidence: 79%
“…[8] In the lanthanide row, Fedushkin and coworkers have presented extensive work on redox-active ligands supporting lanthanides, [9][10][11][12] such as the recent case of rare earth-dpp-Bian compounds (RE=Yb, Tm, or Dy) (dpp-Bian = 1,2-bis[(2,6-diisopropylphenyl)-imino]acenaphthene). [13] Mazzanti and co-workers have recently reported an exciting example where a cerium derivative supported by the LO 3 ligand framework (LO 3 = 1,3,5-(2-OSi(OtBu) 2 C 6 H 4 ) 3 C 6 H 3 ) has been isolated and characterized in four different redox states. [14] In this example, the central arene is redox active, storing electrons in delta bonds and facilitating this rich redox chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…For example, J. Arnold has demonstrated that storing two electrons in a bipyridine ligand facilitates reductive elimination at a thorium(IV) centre [8] . In the lanthanide row, Fedushkin and co‐workers have presented extensive work on redox‐active ligands supporting lanthanides, [9–12] such as the recent case of rare earth‐dpp‐Bian compounds (RE=Yb, Tm, or Dy) (dpp‐Bian=1,2‐bis[(2,6‐diisopropylphenyl)‐imino]acenaphthene) [13] . Mazzanti and co‐workers have recently reported an exciting example where a cerium derivative supported by the LO 3 ligand framework (LO 3 =1,3,5‐(2‐OSi(OtBu) 2 C 6 H 4 ) 3 C 6 H 3 ) has been isolated and characterized in four different redox states [14] .…”
Section: Introductionmentioning
confidence: 99%
“…If the definition of lanthanoid pseudo‐Grignard compounds is extended to Ln II L(X) where L=N or O donor, then more known complexes fall into this category. For example, pseudo‐Grignard complexes, [Sm(dpp‐Bian)(dme)Br] 2 {dpp‐Bian=1,2‐bis[(2,6‐diisopropylphenyl)imino]acenaphthene}, [13] [Eu(dpp‐Bian)(dme)(μ‐X)] 2 (X=Cl, Br), [14] [Yb(dpp‐Bian)(dme)(μ‐Br)] 2 , [15a] [Yb(dpp‐Bian)I(thf) 2 ] 2 , [15b] [Sm(ArO)(μ‐I)(thf) 3 ] 2 , [16] (Ar=C 6 H 2 Bu t 2 ‐2,6‐Me‐4), [Sm(Ap)I(thf) 2 ] 2 , [17] {ApH=(2,6‐diisopropylphenyl)‐[6‐(2,4,6‐triisopropylphenyl)pyridine‐2‐yl]amine}, [Yb(Ap)I(thf) 2 ] 2 , [17] [YbDmp(Tph)N 3 Cl(thf)] 2 , {Dmp=2,6‐Mes 2 C 6 H 3 , Tph=2′,4′,6′‐triisopropylbiphenyl‐2‐yl}, [18] have been were synthesized previously by a variety of routes.…”
Section: Introductionmentioning
confidence: 99%